COVID‐19 associated EBV reactivation and effects of ganciclovir treatment. Issue 4 (10th March 2022) - Meng, Mei; Zhang, Sheng; Dong, Xuan; Sun, Wenqing; Deng, Yunfeng; Li, Wenzhe; Li, Ranran; Annane, Djillali; Wu, Zhixiong; Chen, Dechang
Abstract: Background: Systemic reactivation of Epstein–Barr virus (EBV) may occur in novel coronavirus disease 2019 (COVID‐19) caused by the severe acute respiratory syndrome coronavirus‐2 (SARS‐CoV‐2). However, the clinical consequences of EBV reactivation remain uncertain. Methods: In this retrospective study, we screened 1314 patients with confirmed COVID‐19 who died or were discharged between January 1, 2020 and March 12, 2020, in Wuhan Infectious Disease Hospital, Wuhan, China. Patients who had complete data for EBV serology and cytomegalovirus (CMV) serology were eligible. Serum levels of viral capsid antigen (VCA)‐immunoglobulin G (IgG), Epstein–Barr nuclear antigen‐IgG, VCA‐IgM, early antigen (EA)‐IgG, CMV‐IgG, and CMV‐IgM were compared between survivors and nonsurvivors. Dynamic changes of laboratory tests and outcomes were compared in patients with and without ganciclovir treatment. We used 1:1 matching based on age, gender, and illness severity to balance baseline characteristics. Results: EBV reactivation was present in 55 of 217 patients. EBV reactivation was associated with age (57.91 [13.19] vs. 50.28 [12.66] years, p  < .001), female gender (31 [56%] vs. 60 [37%], p  = .02). Patients with EBV reactivation have statistically nonsignificant higher mortality rate (12 [22%] vs. 18 [11%], p  = .08). EA‐IgG levels were significantly higher in nonsurvivors than in survivors (median difference: −0.00005, 95% confidence interval, CI [−3.10, 0.00], p  = .05). As compared to patients with COVID‐19 who did not receive ganciclovir therapy, ganciclovir‐treated patients had improved survival rate (0.98, 95% CI [0.95, 1.00] vs. 0.88, 95% CI [0.81, 0.95], p  = .01). Hemoglobin ( p  < .001) and prealbumin ( p  = .02) levels were significantly higher in ganciclovir‐treated patients. Conclusion: A high proportion of COVID‐19 patients had EBV reactivation that may be associated with an increased risk of death. Whether treatment with ganciclovir may decrease the mortality of COVID‐19 patients complicated with EBV reactivation warrants to be addressed in a placebo‐controlled randomized trial in the future. Abstract : A high proportion of coronavirus disease 2019 (COVID‐19) patients had Epstein–Barr virus (EBV) reactivation that may be associated with an increased risk of death. Whether treatment with ganciclovir may decrease the mortality of COVID‐19 patients complicated with EBV reactivation warrants to be addressed in a placebo‐controlled randomized trial in the future.